Ownership structure, innovation to firm value with the financing decision as mediation - HMA Rasyid HS Umrie; Yuliani Yuliani (Universitas Hayam Wuruk Perbanas, 2014)
The purpose of this study is to obtain empirical evidence of the influence between the ownership structure and innovation on firm value, funding decisions as mediation of ownership structure and innovation influence on firm value. The populations of this study are all companies listed in Indonesia Stock Exchange. Sampling method used is purposive sampling technique, selected 17 companies based on the criteria. The unit of analysis of this study is a data pooling as many as 85 cases. Methods of data analysis using Structural Equation Modeling (SEM) in variance based. The findings of the study were the higher ownership structure does not contribute to the increase in firm value. The higher the innovation, firm value has increased. Rule of the financing decisions is not mediating the effect of ownership structure on firm value, while the financing decisions proved to be a partial mediation as the effect of innovation on firm value.